Vaginal hysterectomy in the treatment of genital prolapse (our experience). - Tregear Castro, Horacio (2015)
170 cases of genital prolapse, trotados with complementary vaginal hysterectomy, in the Gynecology Department of the Central Hospital No. 2 of the Social Security of Peru, between 1964 and 1973 are reviewed has been practiced vaginal hysterectomy especially in female carriers of cistorectocele, who are in the fourth decade or longer life and less women who have had uterine pathology to justify it. It has been minimal morbidity and no mortality, so it is recommending its application in daily gynecological practice.